Organizing Strategy of Pokgiat as a Community Development Institution in Artotambang Sub-Village - Rahman, Khoirul (Prospect Publishing, 2025)
Artotambang is a sub-village that has an illegal sand and stone mining area in its territory. Seeing the mining assets operating in their area, the community then formed a community activity group (pokgiat) as an institution authorized to manage, secure and develop these assets. They then developed these assets through various businesses under the Sub-Village-Owned Enterprise (BUMDus). This research aims to look at the scheme and strategy of organizing “pokgiat” through the perspective of Resource Mobilization Theory. The method used is qualitative with a case study approach. The types of data used are primary and secondary data. While the data collection technique involves three main methods: interviews, observation, and documentation. The results of this study show that the community activity group and BUMDus of Artotambang have successfully mobilized various types of resources to manage and develop their sand mining levy assets. This success can be seen from their ability to effectively manage human, material, non-material and organizational resources. In addition, the organization has also had a positive impact on economic and social aspects. The economic aspect can be seen from the increase in income and community welfare. Meanwhile, the social aspect can be seen from the close social cohesiveness. However, although these two groups have provided great benefits to the community, there are major critical notes and suggestions that need to be considered to maintain the sustainability of these groups, these notes are mainly regarding: institutional legality, potential conflicts, regeneration mechanisms, and transparency and accountability. .